Pengaruh Persepsi Konsumen pada Iklan Televisi terhadap Minat Beli Produk Mie Sedaap White Curry Studi pada Mahasiswa Fakultas Ekonomi Kampus I Universitas Sanata Dharma - Cicilia Astri Putriwita (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2020)
This research was conducted to know the consumer perception on television advertising toward the buying interests of the customer. The research was done in August 2017 at the Faculty of Economics Campus 1 Sanata Dharma University, Yogyakarta. The research’s target is the Faculty of Economics’ students who have watched the advertisement of the product “Mie Sedaap White Curry” in the television, but they have not bought it yet. The samples were taken using nonprobability sampling technic. The data was obtained from questioners given to 100 respondences. The validity test was processed using Product Moment technic and the reliability test was done with Cronbach Alpha formula. Data analysis technic for this research is the simple regression analysis. In conclusion, this research resulted that consumer perception toward television advertising gave positive influence to the buyer interests.